Glyoxylate cycle and alternative carbon metabolism in metabolic flexibility and pathogenicity of Candida glabrata - Chew, Shu Yih (2019)
Distinct microenvironments in the host can differ significantly (e.g. nutrients availability) and that Candida glabrata, in order to be an effective human pathogen, must transit between these niches and adapt to the differences. In addition, most of the immune cells also actively deprive nutritional resources from invading pathogens, which makes the survival of intracellular pathogens even more challenging. Candida glabrata appears to utilise unique stealth, evasion and persistence strategies in subverting the onslaught of host immune response during systemic infection. In fact, it is surprising that C. glabrata triggers its own engulfment by macrophages. Considering the glucose-deficient condition within the macrophages, C. glabrata must be able to assimilate endogenous resources such as alternative carbon sources for their survival. The present study concentrated on the impact of alternative carbon metabolism in the metabolic flexibility and pathogenicity of C. glabrata. Growth on alternative carbon sources such as acetate, lactate, ethanol and oleic acid induced alteration in several fitness and pathogenic attributes of C. glabrata. These include the reduction in planktonic growth, biofilm formation, and oxidative stress resistance. Alternative carbon sources also modulated the cell wall architecture of C. glabrata, as demonstrated by the reduction of β-glucan and chitin layer, and the increase of mannan layer. Furthermore, the antifungal resistance of C. glabrata grown in alternative carbon sources was significantly enhanced. The metabolic regulation of alternative carbon metabolism in C. glabrata was subsequently explored using high-throughput transcriptomic and proteomic analyses in response to acetate, an alternative carbon source that has been proven to be relevant in vivo. Collectively, both transcriptome and proteome data revealed that the regulation of alternative carbon metabolism in C. glabrata substantially resembled human fungal pathogens such as Candida albicans and Cryptococcus neoformans, with up-regulation of many proteins and transcripts from the glyoxylate cycle and gluconeogenesis, namely isocitrate lyase (ICL1), malate synthase (MLS1), phosphoenolpyruvate carboxykinase (PCK1) and fructose 1,6- biphosphatase (FBP1). In the absence of glucose, C. glabrata shifted its metabolism to hexose anabolism from the available carbon source. The results essentially suggest that the gluconeogenic metabolism are possibly critical for the survival of phagocytosed C. glabrata within the glucose-deficient macrophages. The importance of the glyoxylate cycle enzyme gene ICL1 in the metabolic flexibility and pathogenicity of C. glabrata was further substantiated by the comprehensive analyses of icl1Δ mutant strains. Indeed, disruption of ICL rendered C. glabrata unable to assimilate several alternative carbon sources, as well as reduced its biofilm formation capability. In addition, ICL1 is also pivotal for the survival of phagocytosed C. glabrata, as the icl1Δ mutant strains were significantly more susceptible to macrophage killing relative to wild-type strain. Finally, evaluation of icl1Δ mutant strains in a mouse model of invasive candidiasis showed that ICL1 is essentially required for the full virulence of C. glabrata in vivo. In conclusion, the present study demonstrated that alternative carbon metabolism and the glyoxylate cycle is crucial for the metabolic flexibility and pathogenicity of C. glabrata in vitro and in vivo. The findings implicate ICL1 as a promising target in the development of novel and innovative treatments for a better management of invasive candidiasis.